Analisis Pembelajaran Berdiferensiasi dan Keterampilan Sosial-Emosional dalam Meningkatkan Hasil Belajar IPS Terpadu di SMP Negeri 2 Silimakuta - Remika Pittaomas Purba; Mariah Sonangguk, Corry, Ease Arent (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of differentiated learning and social- emotional skills in improving student learning outcomes at SMP Negeri 2 Silimakuta. The research method used is descriptive qualitative with a case study approach. The findings indicate that social studies teachers have applied differentiated learning through five stages: content differentiation, process differentiation, product differentiation, creating a supportive learning environment, and utilizing technology. Additionally, the application of social emotional skills focuses on five main dimensions: self-awareness, self management, social awareness, relational skills, and responsible decision making. The integration of differentiated learning and social-emotional skills has been proven effective in enhancing student engagement, improving student achievement, and developing character and leadership. This research shows that appropriate teaching strategies can positively impact students' academic performance and character development.